2022
DOI: 10.2147/cmar.s348981
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR Based Metabolomics Technology Identifies Potential Serum Biomarkers of Colorectal Cancer Lung Metastasis in a Mouse Model

Abstract: Background Lung metastasis is a common metastasis site of colorectal cancer which largely reduces the quality of life and survival rates of patients. The discovery of potential novel diagnostic biomarkers is very meaningful for the early diagnosis of colorectal cancer with lung metastasis. Methods In the present study, the metabonomic profiling of serum samples of lung metastasis mice was analyzed by 1 H-nuclear magnetic resonance ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Also, there are some pathways that are identified in two clusters, which cannot be selected if the whole cancer group is compared with the controls. For example, biosynthesis of unsaturated fatty acids , a pathway of interest in colorectal cancer, is selected for both clusters-1 and clusters-2, but the pathway is not selected if the whole cancer group is compared with the controls . The other pathways of interest that are selected by the present heterogeneity analysis include alpha-linolenic acid metabolism , which affects the mitochondrial protein import pathway and the citric acid cycle pathway; thus, it is of interest as a potential target for colorectal cancer prevention .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there are some pathways that are identified in two clusters, which cannot be selected if the whole cancer group is compared with the controls. For example, biosynthesis of unsaturated fatty acids , a pathway of interest in colorectal cancer, is selected for both clusters-1 and clusters-2, but the pathway is not selected if the whole cancer group is compared with the controls . The other pathways of interest that are selected by the present heterogeneity analysis include alpha-linolenic acid metabolism , which affects the mitochondrial protein import pathway and the citric acid cycle pathway; thus, it is of interest as a potential target for colorectal cancer prevention .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, biosynthesis of unsaturated fatty acids, a pathway of interest in colorectal cancer, is selected for both clusters-1 and clusters-2, but the pathway is not selected if the whole cancer group is compared with the controls. 31 The other pathways of interest that are selected by the present heterogeneity analysis include alpha-linolenic acid metabolism, which affects the mitochondrial protein import pathway and the citric acid cycle pathway; thus, it is of interest as a potential target for colorectal cancer prevention. 32 The present results showed that for a similar disease the dci-MSEA-based heterogeneity analysis may highlight samples from different clusters with their own potential disease-related mechanism.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%